Fabrication, characterization, and in vivo biocompatibility evaluation of titanium-niobium implants - Yolun, Abdurrahman; Simsek, Murat; Kaya, Mehmet; Annac, Ebru Elibol; Kom, Mustafa; Cakmak, Omer (Sage Publications Ltd, 2021)
In this study, biocompatible titanium-niobium (Ti-Nb) alloys were fabricated by using powder metallurgy methods. Physical, morphological, thermal, and mechanical analyses were performed and their in vivo compatibility was evaluated. Besides alpha, beta, and alpha '' martensitic phases, alpha+beta Widmanstatten phase due to increasing sintering temperature was seen in the microstructure of the alloys. Phase transformation temperatures of the samples decreased as Nb content increased. The ratio of Nb in the samples affected their mechanical properties. No toxic effect was observed on implanted sites. This study shows that Ti-Nb alloys can be potentially used for orthopedic applications without any toxic effects.
Keywords: Powder metallurgy; TiNb alloys; biomaterial; biocompatibility; implant